Effect of carbon dioxide and cold anaesthesia on the hoarding behavior of the honeybee. - Mardan, Makhdzir; Rinderer, T. E. (1980)
Hoarding behaviour of groups of newly emerged adult honeybees was measured after they had been exposed to CO2 for 10 min, or exposed to CO2 for long enough to immobilize them, or exposed to cold. Both CO2 and cold affected hoarding behaviour. Bees exposed to CO2 for 10 min initially hoarded less, and later hoarded more, than controls. The hoarding rate of bees exposed to CO2 only long enough to immobilize them, or exposed to cold, was generally depressed throughout the experiment. Due to the complex changes in hoarding that follow CO2 treatment, cold is judged to be the preferred anaesthetic for use in hoarding experiments.